Analisis Kesalahan Mahasiswa dalam Menyelesaikan Permasalahan Aljabar Boolean Berdasarkan Teori Kastolan - Sari, Dian Kartika (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2023)
Boolean algebra is a branch of mathematics that has many applications, especially in computer science, engineering, and information technology. Boolean algebra is one of the materials taught in discrete mathematics courses. However, students still feel that this material is quite difficult. Therefore, the solution to this problem is to analyze/describe the difficulties students feel. This research aims to describe students' mistakes in solving Boolean algebra problems based on Castolan theory. This study uses a qualitative method. The research subjects were 43 Informatics Engineering students at the Telkom Institute of Technology Purwokerto 2022/2023. The data collection technique uses a Boolean algebra ability test. Data were analyzed based on the Castolan error procedure. The results of this research showed that the percentage of conceptual errors was 33%, the percentage of procedural errors was 23%, and the percentage of technical errors was 44%. Several factors that cause students to make mistakes when solving problems include: 1) Students' lack of understanding of the problems they face, so they become confused when trying to solve them; 2) Lack of accuracy in the calculation process, which causes errors in their answers; 3) Students' inability to convert problems into mathematical models; 4) Lack of student knowledge about the stages needed to solve problems. Lecturers can utilize the results of this research to develop more effective teaching strategies and support students in overcoming difficulties they may encounter.